New Results on Robust Model Predictive Control for Time-Delay Systems with Input Constraints - Qing Lu; Yiyong Sun; Qi Zhou; Zhiguang Feng (Journal of Applied Mathematics)
This paper investigates the problem of model predictive control for a class of nonlinear systems subject to state delays and input constraints. The time-varying delay is considered with both upper and lower bounds. A new model is proposed to approximate the delay. And the uncertainty is polytopic type. For the state-feedback MPC design objective, we formulate an optimization problem. Under model transformation, a new model predictive controller is designed such that the robust asymptotical stability of the closed-loop system can be guaranteed. Finally, the applicability of the presented results are demonstrated by a practical example.